Analisis Dan Perancangan Sistem Pendukung Keputusan Pemberian Kredit Usaha Pada Bank BNI Kota Jambi Dengan Metode Simple Additive Weighting (SAW) - Siregar, Rizky Maulana; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2021)
Bank BNI Kota Jambi in giving business credit still get trouble, such as: Data management business credit provision for retail customers takes time and occasionally there are a mistake in judgment customers to, business credit provision and the absence of decision systems business credit provision to customers who can give a rough estimate appropriately and quickly. The purpose of research is analyzing and design decision support system with Simple Additive Weighting (SAW) method using PHP programming language and MySQL database. Metodology of this research use waterfall model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can featuring population customer data, criteria data, scoring data that is structured and display report necessary. Research advice are prototyped this system should be devised well and properly so that it will could be applied to Bank BNI Kota Jambi